Fostering Employee Job Satisfaction in The Hospitality Industry: The Role of Organizational Culture, Motivation, and Appraisals Mediated by Service Innovations Case of Hotels in Bali - Hatidja, St; Syahribulan, Syahribulan; Thaha, Salmiyah; Jamaluddin, Jamaluddin; Azizurrohman, Muhammad (STI Policy and Management Journal, 2024)
This study examines how organizational culture, employee motivation, and performance appraisal impact job satisfaction, moderated by the work environment, within Bali’s hotel industry. Using a structured questionnaire, data from 305 employees were analyzed with SmartPLS to assess validity, reliability, and test hypotheses. Results reveal that organizational culture, employee motivation, and performance appraisal significantly enhance job satisfaction. The work environment strengthens these relationships, shown by path coefficients of 0.242 for culture, 0.136 for motivation, and 0.467 for appraisal. Findings underscore the importance of a supportive work environment in maximizing HRM efforts. Managers should cultivate a positive culture, motivate employees, and ensure fair appraisals to improve satisfaction, retention, and service quality. Self-reported data may introduce bias, limiting the generalizability across different hotel settings